Healer Architecture - the Survival of Industrial Buildings - Szatmári, Zsófia (International Journal of Engineering and Management Sciences, 2017)
Protection of industrial buildings can be observed in Western Europe from around the 1970s, technically it was born on the concept of industrial heritage. Industrial archeology was created in Anglo-Saxon areas, which is getting a deal with valued lying areas of the city, related to „rust zones”. [1] The industrial buildings have particular historical value, nevertheless, this day will be very tight space within the scope of protection of monuments. However, often the monument protection does not guarantee the survival because of the lack of investor demand, money and the pursuit of rehabilitation. It’s become a big deal with rehabilitation that the most of us considered the abandoned industrial buildings as ruins.